(untitled) (Fiep Bulletin - online, 2013)
The aim of this study was to evaluate the effects of the Multiprofessional Program Treatment of Obesity (MPTO) on the psychological aspects and quality of life (QoL) in adolescents. Participated in the study 32 adolescents, divided in Intervention Group (IG), that participated by 16 weeks of MPTO and Control Group (CG) that were entering in MPTO. The instruments used were the PedsQL 4.0 and PSDQ respectively to evaluate QoL and physical self-description. The values proposed by Cole et al were used as reference to characterize the obesity in the groups. The Student t test was applied in order to compare the goups IG and CG. The results of the study revealed an BMI average of 30,21 (±5,54) kg/m² in IG and 30,39 (±4,50) kg/m² in CG. The comparison of the adolescents’ physical self-description in the two groups, demonstrated significant differences among the scales Status of Health, Habitual Physical Activity and Body Fat, all for p<0,05. In relation to QoL, the statistical comparison presented significant differences among the groups in the scales Health and Habitual Activities and School Relationships. The comparisons with other studies revealed the potential of MPTO on QoL and their participants physical self-description, it is a clear way to indicate the MPTO as a important strategy for the obese adolescents treatment.